Integrating Waqf and Blue Economy for Sustainable Development in Indonesia: an Analytic Network Process (ANP) Approach - Mongkito, Abdul Wahid; Putra, Trisno Wardy; Alwahidin, Alwahidin; Sikki, Kaisar Lahiya; Rais, Mohammad (UIN Sunan Kudus, 2025)
Waqf is a potential Islamic economic instrument to support sustainable development, while the blue economy offers a welfare-based marine conservation approach. This study aims to integrate both as a development strategy in Indonesia using the Analytic Network Process (ANP) method to systematically determine policy priorities. The data for this study were obtained from nine experts comprising regulators, academics, and practitioners who were selected based on their competence and understanding of strategic issues in waqf management. The results of the analysis show that low nazhir capacity, limited data, and minimal business innovation are the main obstacles. Priority solutions identified include strengthening sectoral policies, improving human resource competencies, and developing waqf business models. The most superior strategies are based on data, research, and technology. These findings indicate that the integration of waqf and the blue economy can be an innovative approach in supporting the Sustainable Development Goals, by encouraging cross-sector collaboration and value-based policies. This study contributes to the integrative literature and can be a reference in formulating waqf-based sustainable maritime development policies